Experiments with realism in contemporary feminist theatre in Britain - Greenstreet, HC (2021)
This thesis re-encounters classic texts of feminist theatre theory by Elin Diamond, Jill Dolan, Sue-Ellen Case and Elaine Aston in the light of formally experimental theatre by women in the 2010s. In particular, it revisits the feminist critique of realism, which characterised realism as an inherently conservative form. Although the critique has been challenged and nuanced since the 1980s, including by its original proponents, I suggest that a political suspicion of realism continues to underlie many critical approaches to theatrical form in contemporary theatre studies, particularly feminist ones.